The Correlation Between Students’ Reading Habits and Their Public Speaking Performance in EFL - Putu Krisna Purnayasa; Ni Made Ratminingsih; Made Hery Santosa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the correlation between students’ reading habits and their public speaking performance in an English as a Foreign Language (EFL) context. The study was motivated by the need to understand how literacy practices contribute to the development of productive language skills, particularly in speaking. A quantitative correlational research design was employed, involving 40 eleventh-grade students of SMK PGRI 2 Denpasar selected through purposive sampling. Data were collected using a reading habit questionnaire and a public speaking performance assessment rubric. The data were analyzed using descriptive statistics and Pearson Product-Moment Correlation after fulfilling prerequisite tests, including normality, homogeneity, and linearity. The results showed that students generally demonstrated high levels of reading habits (M = 82.15) and public speaking performance (M = 87.45). More importantly, the correlation analysis revealed a strong and statistically significant positive relationship between the two variables (r = 0.732, p < 0.05). This indicates that students with higher reading engagement tend to achieve better performance in public speaking tasks. The findings support the theoretical assumption that reading provides essential linguistic input, including vocabulary and discourse structures, which can be transferred into speaking performance. However, the results also suggest that reading habit is not the sole determinant, as other factors may influence speaking ability. This study highlights the importance of integrating reading and speaking activities in EFL instruction to enhance students’ communicative competence.